Community Service About the Risk of Degenerative Diseases and Infections in Aru Surabaya Student Association (HIMAS) Dorms - Dr. Rahayu Anggraini, SKM., M.Si Anggraini; Handayani Handayani; Eppy Setiyowati; Rofi’usyani Rofi’usyani; Ebeth Jeremy Selly; Melky Malae (Journal of Health Community Service, 2022)
The Aru Surabaya Student Association (HIMAS) dormitory is inhabited by 32 students from Maluku who are currently studying in Surabaya. Most students who are living in this dormitory have habits of smoking and heavy coffee. Smoking can cause health problem if it is done exscesively. Health problems that can occur generally are degenerative and infectious diseases, such as coronary heart disease, diabetes mellitus, and the risk of lung infection. Second, the method used in this PPM was health education and laboratory examinations to determine whether there is a risk of coronary heart disease, diabetes mellitus, and lung infection. Third, the seminar’s results of CHD risk, DM, and Pneumonia, on the pre and post-test CHD results there was an increase in understanding of 60%, and the pre and post-test DM results there was an increase in understanding of 50%, while the laboratory screening results on the Fasting Blood Glucose and HbA1c test, had a 35% risk of Diabetes Mellitus (7/20), total cholesterol and hs-CRP tests had a 60% risk of coronary heart disease (10/20) and throat swab test results on Blood Agar and CRP media have a risk of developing pulmonary pneumonia by 40% (8/20). Fourth, in conclusion, students at HIMA Dormitory consisting of adult men with smoking and heavy coffee habits have a 60% risk of coronary heart disease, 35% diabetes mellitus, and 40% lung pneumonia. As a step of PPM sustainability, it is necessary to periodically hold local institutions or health centers to provide counseling and laboratory examinations, so that in the future students in the HIMAS dormitory as the nation's next-generaion can be completely healthy physically and mental.